Increasing Teachers' Creativity Through Strengthening Mutual Cooperation and Work Motivation - Ponijan Ponijan; Dian Wulandari; Soewarto Hardhienata (Riviera Publishing, 2025)
Teacher innovation is the key to improving the quality of learning. Although work motivation, organizational support, and creativity have been proven to influence teachers' innovation, there are still few integrative approaches that consider local wisdom such as gotong royong, a typical Indonesian cultural value. This research aims to develop and optimize a model that maps the role of mutual cooperation and work motivation in encouraging teacher innovation, to support strategic decision-making in the field of education. With a mixed-method approach, data were collected from 180 foundation permanent teachers (GTY) at private high schools in Bekasi Regency. The analysis was carried out using PLS-SEM, with validation of factor and path coefficients to optimize the model. The results showed that mutual cooperation had a significant direct effect on teachers' innovation (? = 0.180; p = 0.002) and work motivation (? = 0.623; p = 0.000), while work motivation was a strong predictor of teacher innovation (? = 0.766; p = 0.000). This research confirms that the culture of mutual cooperation and work motivation plays a strategic role in educational innovation. The integrated model developed is a new contribution to the management of teacher innovation based on culture and psychology and can be used in continuous education policies.